Implementation of Character Installation I Students through Online PPKN Learning with the Jagaratu Application during the Covid-19 Pandemic 19 in SMKN 3 Salatiga - Priska Oktaviani; Nani Mediatati (Edumaspul: Jurnal Pendidikan, 2022)
The purposes of this study are 1) to find out and describe the implementation of character instilling in students through online Civics learning with the Jagaratu application during the Covid 19 pandemic at SMK N 3 Salatiga, 2) to find out the effectiveness of implementing character instilling in students through PPKn learning online with the jagaratu application during the covid 19 pandemic at SMK N 3 Salatiga. This research is a qualitative descriptive research with Civics teachers as subjects and students in class X TSM 2, XI M 1 and XII W 1, totaling 107 students. Data collection technique using techniques observation, interviews, questionnaires, documentation and research instruments. Data analysis techniques in this study were analyzed through techniques analysis qualitative data which include reduction, data display, conclution drawing/verification). (1) The results of the study show that the implementation of character cultivation is carried out through inculcation, exemplary, facilitation, and skills development methods, (2) The character values instilled by the teacher are religious, honest, tolerant, disciplined, hard work, creative, independent, democratic, friendly / communicative, love peace, love to read, care for the environment, care socially, and be responsible, (3) The effectiveness of implementing character building in students through online Civic Education learning with the jagaratu application during the Covid 19 pandemic at SMK N 3 Salatiga in class X TSM 2, XI M 1, and XII W 1 were stated to be quite effective based on the results of the questionnaire at 85.6%.